2021
DOI: 10.1186/s41239-021-00278-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring predictors of instructional resilience during emergency remote teaching in higher education

Abstract: In 2020, Higher Education institutions were pressed to swiftly implement online-based teaching. Among many challenges associated with this, lecturers in Higher Education needed to promptly and flexibly adapt their teaching to these circumstances. This investigation adopts a resilience framing in order to shed light on which specific challenges were associated with this sudden switch and what helped an international sample of Higher Education lecturers (N = 102) in coping with these challenges. Results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 56 publications
1
22
0
2
Order By: Relevance
“…In the literature, numerous studies have been conducted on the emergency remote teaching process carried out during the COVID-19 pandemic. These studies have revealed that students experience various difficulties in time management, motivation, and independent learning while taking courses through the distance education method that they are not used to before, and the quality of education they take is impaired (Lee et al, 2021;Means & Neisler, 2021;Weidlich & Kalz, 2021). Furthermore, the studies examining students' satisfaction with this process have also indicated that students are not very satisfied with emergency remote teaching (Karadag et al, 2021;Simsek et al, 2021;Turan & Gürol, 2020).…”
mentioning
confidence: 99%
“…In the literature, numerous studies have been conducted on the emergency remote teaching process carried out during the COVID-19 pandemic. These studies have revealed that students experience various difficulties in time management, motivation, and independent learning while taking courses through the distance education method that they are not used to before, and the quality of education they take is impaired (Lee et al, 2021;Means & Neisler, 2021;Weidlich & Kalz, 2021). Furthermore, the studies examining students' satisfaction with this process have also indicated that students are not very satisfied with emergency remote teaching (Karadag et al, 2021;Simsek et al, 2021;Turan & Gürol, 2020).…”
mentioning
confidence: 99%
“…In this situation, both the lecturers and students faced numerous challenges, making it more challenging to generate and maintain satisfaction than under normal conditions. Weidlich and Kalz (2021) [ 63 ] applied the resilience perspective to the experiences of the higher education lecturers. They found that the shift to online teaching and learning at higher education institutes, upon the outbreak of Covid-19, was influenced by the personality traits of the lecturers, as well as their previous experience.…”
Section: Discussionmentioning
confidence: 99%
“…To discover new predictors that may encourage teachers to continue intention to use online instruction, even in an uncertain working environment, as well as their impediments to accepting it. (Weidlich & Kalz, 2021) 2021…”
Section: Studymentioning
confidence: 99%